Implementation of a standardised sign-up process to increase MyChart enrolment among HIV-positive patients - Rachel Sigler; Ryan Kubat; Angie Lopez; Jessica R Newman (BMJ Open Quality)
Interactive patient portals are a valuable tool for engaging patients in their healthcare, with various functionalities including viewing laboratory results, refilling prescriptions and communicating directly with nurses, physicians and other healthcare providers via electronic messaging. The utility of patient portals is limited primarily from lack of patient uptake and enrolment due to a variety of factors including lack of awareness, low health literacy, poor technology mastery, lack of availability of a smartphone or computer and distrust of the security of their personal health information. We aimed to increase enrolment in the Epic (O2) MyChart patient portal among patients receiving HIV care through our Infectious Diseases clinic via a standardised sign-up protocol during their clinic visits. This intervention resulted in a modest increase in enrolled patients. However, the factors preventing a more dramatic increase in patient uptake remain unclear.